PERANAN KPU DALAM SOSIALISASI PEMILUKADA KEPADA PENYANDANG DISABILITAS DI KOTA BANDAR LAMPUNG - Maria Desti Rita; Hermi Yanzi; Yunisca Nurmalisa (FKIP Unila, 2016)
This research aimed to describe the role of General Elections Commision in informing, accessibility supplying, and improving the participation of disability voter based on PKPU Number 5 Year 2015. The research methodology that was used in this research was qualitative descriptive by using General Elections Commision, PPUA Penca (Central Election Disability Access), and disability as the research subjects. In addition, the data collection techniques that were used in this research were interview guideliness, observation guideliness, and documentation guidliness. On the other hand, the data analysis techniques that were used in this research were credibility test using source of critic, intern critic, and triangulation. The result of this research showed that there are disabilities who are not registered in Final Voter List. In addition, the implementation of socialization is only done to disability who registered in the organization or group of disability, meanwhile there are some of disabilities who are not registered in the organization or group of disabilityTujuan penelitian ini untuk mendekripsikan peranan KPU dalam pemberian informasi, penyediaan aksesbilitas, dan meningkatkan partisipasi pemilih pada penyandang disabilitas sesuai PKPU No 5 Tahun 2015. Metode penelitian yang digunakan dalam penelitian ini deskriptif kualitatif dengan subjek penelitian komisiener KPU, Pusat Pemilihan Umum Akses Penyandang Cacat (PPUA Penca), dan penyandang disabilitas. Teknik pengumpulan data menggunakan pedoman wawancara, pedoman observasi dan pedoman dokumentasi sedangkan analisis data menggunakan uji kredibilitas dengan kritik sumber, kritik intern dan triangulasi. Hasil penelitian ini menunnjukkan masih terdapat penyandang disabilitas yang tidak terdaftar dalam DPT (Daftar Pemilih Tetap) karena KPU kesulitan menjangkau keberadaan mereka. Pelaksanaan sosialisasi hanya dilakukan pada penyandang disabilitas yang tergabung dalam organisasi atau kelompok penyandang disabilitas.Kata kunci : komisi pemilihan umum, penyandang disabilitas, sosialisasi